A RELIGIOUS MEDITATION ON AYODHYA - Panikkar, Raimundo (Journal of Dharma, 2000)
Ayodhya was, and still is, a sacred place for Muslims. They built a mosque on its grounds. Ayodhya has been believed to be a sacred place for Hindus. That is why they (some of them) demolished the mosque. They claim that before the Muslim ’occupation’ on those sacred grounds there was a Hindu temple. It is almost sure that if the Hindu temple was built there (if it was) it was built on a pre-Hindu sacred shrine. We may call it proto-Hindu if we prefer. It is certain that the historical Hinduism of Rama was not there since .the beginnings of time. If that place was sacred, it was sacred before Hinduism, and it will remain sacred after Islam.